Delivery and quantification of hydrogen peroxide generated via cold atmospheric pressure plasma through biological material. (9th October 2019) - Hathaway, H J; Patenall, B L; Thet, N T; Sedgwick, A C; Williams, G T; Jenkins, A T A; Allinson, S L; Short, R D
Abstract: The ability of plasma-generated hydrogen peroxide (H2 O2 ) to traverse bacterial biofilms and the subsequent fate of the generated H2 O2 has been investigated. An in vitro model, comprising a nanoporous membrane impregnated with artificial wound fluid and biofilms of varying maturity was treated with a helium-driven, cold atmospheric pressure plasma (CAP) jet. The concentration of H2 O2 generated below the biofilms was quantified. The results showed that the plasma-generated H2 O2 interacted significantly with the biofilm, thus exhibiting a reduction in concentration across the underlying nanoporous membrane. Biofilm maturity exhibited a significant effect on the penetration depth of H2 O2, suggesting that well established, multilayer biofilms are likely to offer a shielding effect with respect to cells located in the lower layers of the biofilm, thus rendering them less susceptible to plasma disinfection. This may prove clinically significant in the plasma treatment of chronic, deep tissue infections such as diabetic and venous leg ulcers. Our results are discussed in the context of plasma-biofilm interactions, with respect to the fate of the longer lived reactive species generated by CAP, such as H2 O2 .